2479. Varicella Zoster Immune Globulin Is Effective up to 10 Days Following Varicella Exposure in Pregnant Women, Immunocompromised Patients, and Infants: Results From a Large, Open-Label Expanded-Access Program. (26th November 2018) - Levin, Myron; Duchon, Jennifer; Swamy, Geeta K
Abstract: Background: There are more than 300, 000 cases of varicella annually; nonimmune individuals exposed to varicella-zoster (VZ) virus have a high likelihood of developing varicella. VZ immune globulin (VARIZIG ® ) is used for postexposure prophylaxis to prevent or attenuate VZ infection in high-risk individuals. We assessed varicella incidence and severity in high-risk subjects after administration of VZ immune globulin. Methods: This open-label expanded-access program provided VZ immune globulin to physician-identified, high-risk subjects exposed to varicella. Subjects included immunocompromised children/adults, infants (including preterm infants, newborns whose mothers had VZ infection <5 days before or <2 days after delivery, and infants <1 year of age), and pregnant women. VZ immune globulin (125 IU/10 kg [up to 625 IU]) was administered intramuscularly, ideally ≤96 hours, but up to 10 days, postexposure. Incidence of varicella rash and severity (>100 pox, pneumonia, encephalitis) were assessed up to 42 days after administration. Results: The efficacy population ( n = 505) included 263 immunocompromised subjects (32 adults, 231 pediatric), 137 pregnant women, and 105 infants. More than 97% of exposures fit the CDC definition. Varicella incidence was low in immunocompromised subjects (4.5%, n = 12/269), pregnant women (7.3%, n = 10/137), and infants (11.4%, n = 12/105) and was similar when comparing administration ≤ 96 hours vs. up to 10 days postexposure (6.2% vs. 9.4%, respectively). Of 34 subjects with varicella, 54% were exposed in the household; 5 were considered severe. Common adverse events were pyrexia (4%), neutropenia (3%), and headache (3%). There were no product-related deaths and only 1 serious adverse event (serum sickness) considered probably related to VZ immune globulin. Conclusion: Postexposure administration of VZ immune globulin resulted in low rates of varicella in high-risk subjects, regardless of administration timing within 10 days postexposure. VZ immune globulin—which is FDA-approved, recommended by the CDC, and widely available—was well tolerated and safe in high-risk subjects. Disclosures: M. Levin, Merck: Consultant and Scientific Advisor, Consulting fee and Research support. GlaxoSmithKline: Consultant and Scientific Advisor, Consulting fee and Research support. Saol Therapeutics: Consultant and Scientific Advisor, Consulting fee. J. Duchon, Saol Therapeutics: Consultant and Scientific Advisor, Consulting fee. G. K. Swamy, Saol Therapeutics: Consultant and Scientific Advisor, Consulting fee.